RNA-seq Based Transcriptome Analysis Reveals The Cross-Talk of Macrophage and Adipocyte of Chicken Subcutaneous Adipose Tissue during The Embryonic and Post-Hatch Period - Zhao, Haidong; Wu, Mingli; Tang, Xiaoqin; Li, Qi; Yi, Xiaohua; Zhao, Wanxia; Sun, Xiuzhu (Frontiers in Immunology, 2022)
With high fecundity and short production cycle, poultry is one of the important sources of meat. During the embryonic and post hatch period, the higher death rate caused huge economic losses in poultry production. Our previous study showed that chick subcutaneous adipose tissue is an important energy supply tissue besides yolk. Therefore, the metabolic mechanism of subcutaneous adipose tissue in chicks could provide a new perspective of brooding. The objective of the current study was to evaluate the differences between chick subcutaneous adipose tissue and abdominal adipose tissue before and after hatching, and reveal the cross-talk of different cells within chick subcutaneous adipose tissue. The results of RNA-seq and WGCNA of chick subcutaneous and abdominal adipose tissue showed that the function of chick subcutaneous tissue was related to immunoreaction, and macrophage could be the major immune infiltration cell type in chicken subcutaneous adipose tissue, which were also verified by qPCR, HE stain and IHC. The results of FFAs-induced the cross-talk between macrophages and adipocytes showed that FFAs-Ccl2 (chicken CCL26) axis could have an important role in lipid transportation in adipose tissue. The results of Oil red O and Nile red stain demonstrated that macrophage own the ability to absorb FFAs quickly. Interestingly, according to the genomic organization of CCL family with representative vertebrate species, we found that chicken CCL26 could be the major chemokine in chicken adipocyte as the status of CCL2 in mammals adipocyte. In conclusion, we demonstrate that FFAs induced Ccl2 (Chicken CCL26) secretion is crucial in determining fat depot-selective adipose tissue macrophage (ATM) infiltration, which could be an important medium of lipid transportation in chicken subcutaneous adipose tissue. These findings may have multiple important implications for understanding macrophage biology with chick subcutaneous adipose tissue, and provide theoretical basis for lipid metabolism in poultry brooding.